Saving and portfolio allocation before and after job loss - Christoph Basten; Andreas Fagereng; Kjetil Telle (Statistics Norway, Research Department, 2012)
Using administrative panel data from Norway, we investigate the development of household labor income, financial wealth and asset holdings over a nine-year period surrounding job loss. Consistent with a simple theoretical model, the data show precautionary saving and a shift toward safer assets in the years leading up to unemployment, and depletion of savings during unemployment. This suggests that at least some households can foresee and prepare for upcoming unemployment, which indicates that private savings can complement publicly provided unemployment insurance.
Keywords: D12; E21; E24; G11; J65; 330; unemployment; precautionary saving; consumption smoothing; household portfolios; portfolio allocation; optimal unemployment insurance